Analyzed potential vorticity fields for explosive and non-explosive cyclogenesis events during FGGE. - Kirchoffer, Peter J. (1986)
Potential vorticity and jet streak properties associated with 23 explosive and non-explosive cyclones from the western North Atlantic and western North Pacific Oceans are analyzed for the period 17 January to 23 February 1979. ECMWF analyses with FGGE data are used to represent the 300 mb wind fields over these ocean areas. Relative maxima in potential vorticity are present upstream of all cyclones. Storm tracks with respect to the potential vorticity maxima are counter-clockwise with the greatest sea-level pressure decreases occurring when the storm is to the east or southeast of the maximum, whereas pressure falls diminish when the cyclone is north of the maximum. Only five of the 23 cases have a pre-existing potential vorticity lobe that becomes superposed with the surface feature and enhances cyclogenesis. In the remaining cases, the cyclone and potential vorticity lobe propagate and develop concurrently. The presence of a jet maxima over the storm is a major factor in storm development with large pressure falls being directly related to higher 300 mb wind speeds. In 20 of 23 cases, the storm is in the left-front jet quadrant at some time during its development. A statistical analysis demonstrates that forecasting the actual values of 12-h pressure falls from the potential vorticity and wind fields is difficult. However, forecasting development within one of three intensity categories using a discriminate analysis technique may approach 90% accuracy for explosive cyclones. Approved for public release; distribution is unlimited. Lieutenant, United States Navy http://archive.org/details/analyzedpotentia1094521668